2018
DOI: 10.1002/joc.5541
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of climate variability and trends across Arctic Fennoscandia in four reanalyses

Abstract: Observations reveal a statistically significant warming across Arctic Fennoscandia: three reanalyses show a similar regional warming of smaller magnitude while the fourth is anomalous, even having a slight cooling in some areas. Spatial patterns of precipitation trends across the region differ markedly between the reanalyses, which have varying success at matching observations but generally fail to replicate sites with significant observed trends. There is a clear spatial mismatch between reanalyses and observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…We now examine the year-to-year variation of the RFO for each node in each reanalysis to understand the interannual variability and also whether the RFO for particular nodes display any trends. The latter could represent a change in the synoptic climatology of the region, but a large number of studies have identified the potential for spurious trends in reanalyses in the polar regions (Befort et al, 2016;Bromwich & Fogt, 2004;Huai et al, 2019;Marshall et al, 2018;Schneider & Fogt, 2018;Screen & Simmonds, 2011;Wang et al, 2016;Wohland et al, 2019). Figure 4 displays the natural logarithm of the ratio of the RFO for a particular year divided by the mean over the 1980-1999 reference period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We now examine the year-to-year variation of the RFO for each node in each reanalysis to understand the interannual variability and also whether the RFO for particular nodes display any trends. The latter could represent a change in the synoptic climatology of the region, but a large number of studies have identified the potential for spurious trends in reanalyses in the polar regions (Befort et al, 2016;Bromwich & Fogt, 2004;Huai et al, 2019;Marshall et al, 2018;Schneider & Fogt, 2018;Screen & Simmonds, 2011;Wang et al, 2016;Wohland et al, 2019). Figure 4 displays the natural logarithm of the ratio of the RFO for a particular year divided by the mean over the 1980-1999 reference period.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also shown that the quality of reanalyses are hard to quantify at the poles because of the lack of independent data sets and the low density of the observing networks. Nevertheless, studies have displayed poor performance in both the Arctic (Lindsay et al, 2014;Liu & Key, 2016;Marshall et al, 2018;Rapaic et al, 2015;Simmons & Poli, 2015;Screen & Simmonds, 2011) and the Antarctic (Bracegirdle, 2013;Bracegirdle & Marshall, 2012;Bromwich & Fogt, 2004;Bromwich et al, 2007;Fogt et al, 2017;Nygard et al, 2016;Schneider & Fogt, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the shape of the annual cycle is spatially uneven: the wettest seasons are autumn and winter in coastal AF, but inland summer has the greatest precipitation (Achberger and Chen 2006;Jylhä et al 2010). Furthermore, the spatial structures of the annual and seasonal trends are complex, having greatly varying magnitude and sign within short distances (Achberger and Chen 2006;Marshall et al 2018). Mean precipitation trends across AF generally show a wetting in recent decades, such as the increasing snowfall trend in Finnish Lapland (Luomaranta et al 2019), but also with local areas of drying (Aalto et al 2016;Marshall et al 2016Marshall et al , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the spatial structures of the annual and seasonal trends are complex, having greatly varying magnitude and sign within short distances (Achberger and Chen 2006;Marshall et al 2018). Mean precipitation trends across AF generally show a wetting in recent decades, such as the increasing snowfall trend in Finnish Lapland (Luomaranta et al 2019), but also with local areas of drying (Aalto et al 2016;Marshall et al 2016Marshall et al , 2018. Thus, there is a clear need to provide accurate information on how EPEs are changing in AF at a regional scale in order to support the planning of future infrastructure requirements to safeguard both human resources and the natural environment.…”
Section: Introductionmentioning
confidence: 99%
“…Mooring buoy with long‐term and in situ observational data is often used as the true value for evaluating reanalysis products. The discrepancies between observational data and reanalysis products data have been studied in many regions, for example, the tropical Pacific (Weller and Anderson, ; Wang and McPhaden, ), the Atlantic (Moyer and Weller, ; Josey, ; Sun et al, ), Labrador Sea (Renfrew et al, ), Kuroshio Extension region (Kubota et al, ; Tomita et al, ), and other areas (Bourras, ; Swain et al, ; Marshall et al, ). The results of previous studies indicate that the accuracy of these products still needs to be improved, especially those of heat fluxes (Moore and Renfrew, ; Jiang et al, ).…”
Section: Introductionmentioning
confidence: 99%